Antioxidative Properties and Nutritional Contents of Selected Indigenous Microalgae - Mohd Ikhsan, Natrah Fatin (2006)
Microalgae are known to contain various beneficial pigments and are high in nutritional contents. The present studies were done to identify and explore the potential of indigenous microalgae as new natural sources for antioxidants with superior proximate and biochemical values. Fourteen microalgae were isolated, purified and cultured from fresh and brackish waters. The ability of microalgae as natural resources of antioxidants were studied through screening test using three antioxidative chemical assays (ferric thiocyanate (FTC), thiobarbituric acid (TBA) and 1,1’–diphenyl-2-picrylhydrazyl (DPPH)). Preliminary screening results showed that methanol extracts from six microalgae (Isochrysis galbana, Chaetoceros calcitrans, Scenedesmus quadricauda, Chlorella vulgaris, Nannochloropsis oculata and Tetraselmis tetrathele) were active in inhibiting the lipid peroxidation of linoleic acid. Among all the microalgae, I. galbana and C. calcitrans showed highest antioxidative activities (>90%) in FTC and TBA assays indicating possibility of active constituents for the protection from lipid peroxidation. Selected microalgae with high antioxidant values (I. galbana and C. calcitrans) were partitioned into different solvent fractions (hexane, dichloromethane, ethyl acetate, butanol and aqueous extracts) to separate components of wide mixture into group of compounds based on polarity and were re-tested with the antioxidative chemical assays. Dichloromethane extracts of I. galbana and C. calcitrans showed highest level of antioxidative activities with 97.1±0.1% and 97.4±0.1% linoleic acid peroxidation (LAP) inhibition in FTC assays respectively. Similar trends of high level antioxidative activities in these two microalgae were obtained in TBA assays. Effects of selected microalgal extracts on up-regulation of antioxidant enzymes gene expression in murine monocytic macrophage (RAW 264.7) cell lines were studied. Both dichloromethane extracts of I. galbana and C. calcitrans showed high up-regulation in the expression of all antioxidant enzymes genes tested in RAW 264.7. Liquid chromatography-mass spectrometry was employed to identify the constituents which were responsible for all of the antioxidative activities. Fucoxanthin and its isomers were identified as the major constituents in both microalgal species. Finally, nutritional analysis (proximate and biochemical) were done on microalgae with high antioxidative activities (I. galbana and C. calcitrans) in order to investigate their nutritive values. Both microalgae were found to be rich in nutrients with protein: carbohydrate: lipid percentage composition of 47.9±2.5: 26.8±0.2: 14.5±1.4 for I. galbana and 36.4±1.7: 27.4±3.0: 15.5±0.9 for C. calcitrans respectively. Both species contained high level of n-3 HUFA (28.0%±0.7: I. galbana and 28.5%±1.4: C. calcitrans) and n-6 HUFA (6.5%±1.8: I. galbana and 23.0%±2.5: C. calcitrans). Amino acid analyses also showed both microalgae contained high composition of essential amino acids. This study illustrated that some microalgae such as I. galbana and C. calcitrans have the potential for effective natural sources of antioxidants with high nutritional values.